Mitigation of Chlorine Lung Injury by Increasing Cyclic AMP Levels - Hoyle, Gary W. (American Thoracic Society, 2010)
Chlorine is considered a chemical threat agent to which humans may be exposed as a result of accidental or intentional release. Chlorine is highly reactive, and inhalation of the gas causes cellular damage to the respiratory tract, inflammation, pulmonary edema, and airway hyperreactivity. Drugs that increase intracellular levels of the signaling molecule cyclic AMP (cAMP) may be useful for treatment of acute lung injury through effects on alveolar fluid clearance, inflammation, and airway reactivity. This article describes mechanisms by which cAMP regulates cellular processes affecting lung injury and discusses the basis for investigating drugs that increase cAMP levels as potential treatments for chlorine-induced lung injury. The effects of β(2)-adrenergic agonists, which stimulate cAMP synthesis, and phosphodiesterase inhibitors, which inhibit cAMP degradation, on acute lung injury are reviewed, and the relative advantages of these approaches are compared.